Possible solution to smoothen the torque curve of the CAMPRO engine - Mohiuddin, A. K. M.; Rahman, Mohammed Ataur; Alias, Arfah; Farraen, M.A. (2011)
The main objective of this project is to develop new solutions to smoothen the torque curve of the CAMPRO engine. The solutions should be cost effective, reliable and maintain the current emission level. The authors have performed an extensive study on the causes of the torque dip in CAMPRO engine. The CAMPRO engine experiences performance downfall when it reaches at certain rpm. The phenomenon is known as torque dip or torque loss where the output torque is not smooth,consequently formed a dip in the torque curve. The dip which occurs at 2500 – 3500 rpm is mainly influenced by the geometry of the designed intake manifold and valve timing. The main objective of this work is to perform an extensive study on the causes of the dip in CAMPRO engine and subsequently to provide the best solution that will improve the performance. Analysis shows that at the point of dip; a downfall of the volumetric efficiency also occurs. In order to enhance the volumetric efficiency and to eliminate the torque dip, two parameters were considered, viz., runner length & diameter and valve timing. In this paper focus is given on the length of intake manifold. From the analysis done, two possible solutions were provided viz., Dual Length Intake Manifold and Continuous Variable Intake Manifold.